Probation Officers and the Experience of Juvenile Offenders in the Juvenile System - Taufik Mohammad; Azlinda Azman (Kajian Malaysia, 2018)
Probation officers are among the individuals who come in closest contact with juvenile offenders in Malaysia. They have extensive responsibilities in the juvenile justice, such as interviewing the juvenile offenders about their social system, writing a probation report for the court, and making recommendations based on their observations. This makes them reliable figures for ascertaining what is happening in the juvenile system. Based on this, this article argues that it is pivotal to study the perceptions of the probation officers regarding the juvenile experience to understand the effectiveness of the system. In this mixed method study, 12 probation officers from 6 states in Malaysia were interviewed. The close-ended items required them to rate each component of the questionnaire, which are related to aspects of the preparation of offenders for entry into the system, their participation inside the system, and their outcomes. The participants' ratings indicated higher-than-average satisfaction. However, the qualitative data showed a mixed response, with respondents expressing more scepticism about the system and often focusing on external factors. Additionally, the probation officers discussed the importance of modules for the juvenile offenders' benefit upon release. The responses from the probation officers shed light on how the experiences of the juvenile offenders can be improved through a three-layer plan that includes the process of preparation, detention, and release.